Costing the impact of interventions during pregnancy in the UK: a systematic review of economic evaluations - Jane Sandall; Andy Healey; Asma Khalil; Sophie Relph; Louisa Delaney; Alexandra Melaugh; Matias C Vieira; Dharmintra Pasupathy (BMJ Open)
Objective The aim of this review was to summarise the current evidence on the costing of resource use within UK maternity care, in order to facilitate the estimation of incremental resource and cost impacts potentially attributable to maternity care interventions.Methods A systematic review of economic evaluations was conducted by searching Medline, the Health Management Information Consortium, the National Health Service (NHS) Economic Evaluations Database, CINAHL and National Institute for Health and Care Excellence (NICE) guidelines for economic evaluations within UK maternity care, published between January 2010 and August 2019 in the English language. Unit costs for healthcare activities provided to women within the antenatal, intrapartum and postnatal period were inflated to 2018–2019 prices. Assessment of study quality was performed using the Quality of Health Economic Analyses checklist.Results Of 5084 titles or full texts screened, 37 papers were included in the final review (27 primary research articles, 7 review articles and 3 economic evaluations from NICE guidelines). Of the 27 primary research articles, 21 were scored as high quality, 3 as medium quality and 3 were low quality. Variation was noted in cost estimates for healthcare activities throughout the maternity care pathway: for midwife-led outpatient appointment, the range was £27.34–£146.25 (mean £81.78), emergency caesarean section, range was £1056.44–£4982.21 (mean £3508.93) and postnatal admission, range was £103.00–£870.10 per day (mean £469.55).Conclusions Wide variation exists in costs applied to maternity healthcare activities, resulting in challenges in attributing cost to maternity activities. The level of variation in cost calculations is likely to reflect the uncertainty within the system and must be dealt with by conducting sensitivity analyses. Nationally agreed prices for granular unit costs are needed to standardise cost-effectiveness evaluations of new interventions within maternity care, to be used either for research purposes or decisions regarding national intervention uptake.PROSPERO registration number CRD42019145309.